A Clinical Analysis of Thirty-Five Patients Undergoing Aortic Reoperation - Yuanfeng,Xin (2022)
Abstract Introduction: At present, there are few reports regarding the issue of aortic reoperation due to its complexity and high risk and individual differences among patients. Methods: From November 2016 to December 2017, the data from 35 cases of aortic reoperation at our institution, out of 212 consecutive aortic repairs, were reviewed. We retrospectively summarized and analyzed their surgical indications, operative data, time interval from previous aortic repair, and outcomes. The time intervals until reoperation were analyzed for differences. Results: Patients’ mean age was 40.9±14.5 years, and 25 of them were men (71.4%). The indications for reoperation were aortic valvular problem (14.3%), aneurysmal dilatation (25.7%), pseudoaneurysm formation due to anastomotic leakage (43.2%), and aortic dissection (17.1%). For patients who had underwent primarily emergency operations due to aortic dissection, the time interval until reoperation (4.8±3.2 years) was significantly shorter than that of the whole group (5.5±3.6 years, P<0.01). Among the 35 reoperations, Sun’s procedure was selected for 16 patients (45.7%) with total aortic arch reconstruction. The average follow-up was 12 months (range 9-15 months). Hospital mortality was 5.7% (two patients). Among the hospital survivors there were no cases of death, rupture of residual dissection, paraplegia, or central nervous system complications during the follow-up period. Conclusion: Patients with acute aortic dissection required repeat surgery significantly earlier compared to other diseases. As to reoperation strategy, we recommend Sun’s procedure as the choice for extended arch reconstruction since minimal effect on overall mortality and complication rates were found.